The Geophysical Environment of (486958) Arrokoth—A Small Kuiper Belt Object Explored by New Horizons. Issue 6 (15th June 2022) - Keane, James T.; Porter, Simon B.; Beyer, Ross A.; Umurhan, Orkan M.; McKinnon, William B.; Moore, Jeffrey M.; Spencer, John R.; Stern, S. Alan; Bierson, Carver J.; Binzel, Richard P.; Hamilton, Douglas P.; Lisse, Carey M.; et al.
Abstract: NASA's New Horizons mission performed the first flyby of a small Kuiper Belt Object (KBO), (486958) Arrokoth on 1 January 2019. The fast flyby revealed a fascinating, flattened, contact binary replete with a variety of unexpected geologic terrains. However, the irregular shape and constraints imposed by the fast flyby makes it a challenge to understand these features. Here we use the latest New Horizons shape models of Arrokoth to investigate its geophysical environment, including its surface slopes, gravity field, and moments of inertia—which are critical context for understanding Arrokoth's formation, evolution, and peculiar geology. We find that Arrokoth's surface features have a complicated relationship to its geophysical environment. For example, bright material tends to be concentrated in geopotential lows (like the neck), consistent with mass wasting—however, this trend is not consistently observed across Arrokoth. Mass wasting may naturally explain some aspects of Arrokoth's geology, but the actual dynamics of material transport may be complicated owing to Arrokoth's unique shape, spin‐rate, and inferred density. While New Horizons 's fast and distant flyby precluded directly measuring Arrokoth's mass, we used techniques previously pioneered for comets and asteroids to infer its density. We find that Arrokoth has a low bulk density of ρ = 235 kg/m 3 (1 σ range: 155–600 kg/m 3 ). This density is low compared to previously explored small bodies, but is comparable to comets, select binary KBOs, and the ring‐moons of Saturn. This low density may be a critical data‐point for understanding the formation of planetesimals at the dawn of the Solar System. Plain Language Summary: NASA's New Horizons mission performed the first flyby of a small Kuiper Belt Object (KBO), (486958) Arrokoth on 1 January 2019. Arrokoth is a ∼30‐km long, peanut shaped, icy body in the Kuiper Belt—a reservoir of small bodies left over from the Solar System's formation. Arrokoth is the most distant, and likely the least evolved object, ever explored by a spacecraft. Arrokoth's unusual shape makes it challenging to determine how material moves across its surface. We use the latest shape models to calculate Arrokoth's gravity field. Bright material tends to collect in Arrokoth's lowest locations, perhaps indicating material can move downslope. While New Horizons was not able to measure the density of Arrokoth, we are able to infer it using techniques pioneered for studying asteroids and comets. We find that Arrokoth's density is extremely low—more akin to fluffy snow on Earth. If correct, this would be one of the lowest density objects ever explored, closer to the densities of some of the comets and small moons within Saturn's rings. Arrokoth's low density may suggests that the building blocks of planets were assembled very gently in the outer Solar System, in the first few million years of Solar System formation. Key Points: We present new models for the geophysical environment of (486958) Arrokoth based on the latest New Horizons shape models Many (but not all) of Arrokoth's enigmatic surface markings are correlated with its geophysical environment Analysis of Arrokoth's shape suggests that it has a low density of 235 kg/m 3 (1 σ range: 155–600 kg/m 3 )